Performance of small-domain monolithic silica columns in nano-liquid chromatography and comparison with commercial packed bed columns with 2 µm particles - Hara, Takeshi; Izumi, Yoshihiro; Hata, Kosuke; V. Baron, Gino; Bamba, Takeshi; Desmet, Gert (Journal of Chromatography A, 2020)
•Monolithic silica columns with sub-2 µm domain size have been synthesized.•The produced monolith columns provide a high column efficiency (H = ~4 µm).•Peak capacities (np) are 30‒40% higher than in a commercial particle column.•A high repeatability of the performance of the fabricated columns is demonstrated. We report on a direct comparison of the separation performance in capillary nano-LC between commercial packed bed columns and the small-domain silica monoliths in applications. Octadecylsilylated monolithic silica capillary columns with a 50 and 100 µm inner diameter (i.d.) were prepared with a procedure providing domain sizes in the sub-2 µm range. The fabricated monolith columns could provide plate heights (H) of 4.0‒4.2 µm for hexylbenzene (retention factor (k) = 3.6) at an optimal linear velocity range under an isocratic condition, while showing a column permeability (Kv0 = 1.6‒1.8 × 10−14 m2) comparable to that of a column packed with 3‒3.5 µm particles. When the peak capacity (np) for a cytochrome C digest was compared for variable gradient times (tG = 15, 30, 60, and 120 min) and constant gradient steepness (b’), the present monolith columns could show a 30‒40% higher np-value than the packed capillary column with 2 µm particles (e.g. np = 180 versus np = 259 at tG = 30 min). The produced monolith columns showed a high chromatographic repeatability for both isocratic and gradient elution (e.g. relative standard deviation (n = 3, RSD (%)) = 0.5% for H, 2,6% for k, and 5.6% for Kv0 in the isocratic mode using the 100 µm i.d.-columns). The present results show that the domain sizes which can now be achieved for capillary silica monoliths are sufficiently small to result in separation efficiencies that can successfully compete with the commercial packed bed columns available for use in nano-LC applications.